A chemoenzymatic route to chiral siloxanes - Naoum, Ravi; Séguin, Jacqueline P.; Trant, John F.; Frampton, Mark B.; Hudlický, Tomáš; Zelisko, Paul M. (Tetrahedron, 2016)
An approach employing two enzymes—toluene dioxygenase and immobilized lipase B from Candida antarctica (N435)—was explored as a potential biocatalytic method for the coupling of chiral diols with siloxane species. Analysis of reaction mixtures using1H NMR spectroscopy suggested that up to 66% consumption of the siloxane starting materials had occurred. Oligomeric species were observed and chiral products from the coupling of a cyclic diol with a siloxane molecule were isolated and characterized by MALDI-ToF MS and GPC. Immobilized lipases from Rhizomucor miehei and Thermomyces lanuginosus were also explored as potential catalysts for the coupling reactions, however, their use only returned starting material.